Innovation and economic development - Almarzoqi, Raja; Mathis, F. John (Routledge studies in the economics of innovation., 2025)
"Over the past two decades, several sudden, unforeseen, and significant changes have occurred in the world's political and economic landscape. This book explores their impact on the processes of contemporary disruptive innovations during the Fourth Industrial Technology Revolution and the role that global finance and international commerce play. The expansion of multinational corporations, increasing dependence on global supply chains, and the globalization of the world economy have aided the rising expansion of Innovations worldwide. The authors analyze the drivers and relationship between these increasingly dispersed Innovations and the expanding linkage between economic growth in developed and developing countries. Progress will continue with technological innovations in financial services, lowering the cost to consumers and companies. Financial transactions will be executed increasingly by the individual using their cell phone or computer. Electronic digital payments and banking will replace currency. This book focuses on Innovations in advanced countries and examines developments in emerging markets and the implications for the world's future economic growth. The collaborative expansion and dispersion of online education across different cultures impact labor markets, diversity and immigration, and the rise and expansion of women entrepreneurial Innovators. The progression of global access to higher levels of education is changing the culture, values, and institutional foundations supporting Innovation. Knowledge of the expanding Innovation Ecosystems is crucial for understanding contemporary global business and entrepreneurship, international trade and capital flows, and investments impacting world history and economic, social, and political sciences subjects"--